Analisis Dampak Konsep Kebijakan Kerja, Kedisplinan Kerja, Pemberian Insentif Dan Motivasi Terhadap Kinerja Karyawan Pada PTPN III Kebun Rantau Prapat - Indra, Aulia; Munthe, Rika Syahmewa; Siregar, Usmala Dewi (Jurnal Manajemen Akuntansi (JUMSI), 2024)
This study aims to determine the impact of the concept of work policy, work discipline, incentives and motivation on the performance of employees of PTPN III Kebun Rantau Prapat either partially or simultaneously. The population in this study is the employees of PTPN III Kebun Rantau Prapat. Determination of the number of samples using the slovin formula with a total of 98 people . Data analysis methods used are descriptive analysis methods, multiple linear regression analysis, and hypothesis testing. Data collection techniques in the study were obtained by means of Literature Research, Field Research (observation, interviews, and questionnaires).                            The results of partial hypothesis testing (t test) showed that work discipline (X2) and motivation (X4) had a positive and significant impact on employee performance at PTPN III Kebun Rantau Prapat. The results of the simultaneous hypothesis test (test F) showed the concept of work Policy (X1), work discipline (X2), incentives (X3) and motivation (X4) affect the performance of employees at PTPN III Kebun Rantau Prapat. Based on the results of the determination test, it is known that the performance of employees in PTPN III Kebun Rantau Prapat can be explained by the variable concept of work policy, work discipline, incentives and motivation by 22.4%. While the remaining 77.3% can be explained by other variables that are not discussed in this study.